Diseño de un banco de pruebas de velocidades, mecánicas, de automóviles para Cesvi Colombia (2017)
In this project the design of a test bench for gearboxes, mechanical, of automobiles for the company Cesvi Colombia, with the purpose of being able to perform a test of operation to said boxes and to demonstrate the state in which they are, Since when arriving at the facilities of the company its performance and / or functional status is not completely known; Likewise, we sought to offer the customer a guarantee of operation of these automobile components and thus generate additional income to the company. A finite element simulation was carried out in order to identify the behavior of different elements of the structure. This was done using the NX 9.0 software and the results were interpreted analytically.